An improvement of resource consumption in wireless sensor network (WSN) using compressive sensing / Maizatul Akmal Ibrahim and Norkhushaini Awang - Ibrahim, Maizatul Akmal; Awang, Norkhushaini (Universiti Teknologi MARA, 2022)
Wireless Sensor Network (WSN) refers to a group of spatially dispersed and dedicated sensors designed to monitor and record the physical conditions of the environment and organise the data collected at a central location. One of the problems in wireless sensor network (WSN) is the low computational resources available which is the limited battery life of sensor nodes. Hence, one of the ways to prolong the lifetime is to implement Low energy Adaptive Clustering Hierarchy (LEACH). The Compressive Sensing (CS) algorithm has been implemented to the network through Cluster Head (CH) to further the lifetime longevity. CS is a technique utilised for energy efficient data gathering in WSNs. Compressive sensing provides benefits such as robustness, long lifetime of the network, reduced energy consumption, and a simple routing scheme. The simulation testing and algorithm implementation have been done in MATLAB with the scripting language. Through the implementation of CS, it can be concluded that the CS algorithm helps increase the network lifetime by 9.7%.